Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2024)
Where did 2021 go? While COVID-19 once again took control of our lives I find the year seems to have passed very quickly and I wanted to reflect on our accomplishments throughout 2021.